The square root of (2 (10^102)+2 (10^51)+(10^102+10^51)^2+1) can be expressed as 10^(A)+10^(A/2)+1, where A is a positive integer. Find the sum of the prime factors of A. (Hint: This problem can be solved without using a calculator. Think about Pythagorean quadruples, and also think about algebra.)
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Set x = 1 0 5 1 . Then 2 ⋅ 1 0 1 0 2 + 2 ⋅ 1 0 5 1 + ( 1 0 1 0 2 + 1 0 5 1 ) 2 + 1 = 2 x 2 + 2 x + ( x 2 + x ) 2 + 1 = ( x 2 + x ) 2 + 2 ( x 2 + x ) + 1 = [ ( x 2 + x ) + 1 ] 2 Thus, the square root of the given expression is simply 1 0 1 0 2 + 1 0 5 1 + 1 and A = 1 0 2 = 2 × 3 × 1 7 . 2 + 3 + 1 7 = 2 2 .
Problem Loading...
Note Loading...
Set Loading...
The key to this problem is algebra. Take the sum of the three squares 2^2+3^2+6^2. This is equal to 7^2. We can show algebraically that x^2+(x+1)^2+(x^2+x)^2=x^2+x^2+2x+1+x^4+2x^3+x^2=x^4+2x^3+3x^2+2x+1=(x^2+x+1)^2. Now notice that 2(10^102)+2(10^51)+(10^102+10^51)^2+1=10^102+2 10^51+1+10^102+((10^51)(10^51+1))^2. Since x^2+2x+1=(x+1)^2, 10^102+2 10^51+1=(10^51+1)^2. So 10^102+2*10^51+1+10^102+((10^51)(10^51+1))^2=(10^51+1)^2+(10^51)^2+((10^51)(10^51+1))^2. Notice that this is in the form of x^2+(x+1)^2+(x(x+1))^2. So this is equal to (x^2+x+1)^2=(10^102+10^51+1)^2. so the square root of this quantity is 10^102+10^51+1. This is equal to 10^(102)+10^(102/2)+1. So A is equal to 102. The prime factorization of 102 is 2 *3 *17. This implies that the sum of the prime factors of A is 2+3+17= 22 .